2015
DOI: 10.1002/anie.201502836
|View full text |Cite
|
Sign up to set email alerts
|

CoOOH Nanosheets with High Mass Activity for Water Oxidation

Abstract: Endowing transition-metal oxide electrocatalysts with high water oxidation activity is greatly desired for production of clean and sustainable chemical fuels. Here, we present an atomically thin cobalt oxyhydroxide (γ-CoOOH) nanosheet as an efficient electrocatalyst for water oxidation. The 1.4 nm thick γ-CoOOH nanosheet electrocatalyst can effectively oxidize water with extraordinarily large mass activities of 66.6 A g(-1), 20 times higher than that of γ-CoOOH bulk and 2.4 times higher than that of the benchm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
436
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 598 publications
(468 citation statements)
references
References 27 publications
30
436
2
Order By: Relevance
“…In the case of inorganic salts as precursors, a few metal hydroides may have formed through metal ion hydrolysis during solvent evaporation. It is well known that metal hydroxides easily grow into nanosheets owing to their layered structure [15,21,31,32]. Because solvent evaporation is much faster than the hydrolysis of metal ions, the proportion of nanosheets is much lower than that of nanoparticles in the microspheres formed by the subsequent pyrolysis of nitrates.…”
Section: Morphology and Structural Characterizationmentioning
confidence: 99%
“…In the case of inorganic salts as precursors, a few metal hydroides may have formed through metal ion hydrolysis during solvent evaporation. It is well known that metal hydroxides easily grow into nanosheets owing to their layered structure [15,21,31,32]. Because solvent evaporation is much faster than the hydrolysis of metal ions, the proportion of nanosheets is much lower than that of nanoparticles in the microspheres formed by the subsequent pyrolysis of nitrates.…”
Section: Morphology and Structural Characterizationmentioning
confidence: 99%
“…27–36 For example, greatly enhanced catalytic performances have been achieved by the pioneering 2D ultrathin nanosheets made by the Xie, 2730 Wei, 27,28,31 Yang 32 and Zhang 33,34 groups. A huge mass activity for the oxygen evolution reaction has been achieved by well-designed ultrathin CoOOH solid nanosheets.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the overpotential on Co 3 O 4 NSs was also lower than that for many previously reported Co-based catalysts. 19,34,35,43 Moreover, the corresponding Tafel plots (Figure 3c) indicated that the ultrathin Co 3 O 4 NSs possessed a smaller Tafel slope (46 mV/dec) than that of Co 3 O 4 NCs (63 mV/dec). The smaller Tafel slope makes Co 3 O 4 NSs have large current densities at low overpotentials.…”
Section: Results and Discussionmentioning
confidence: 97%